Optimizing Islamic and Character Education Outcomes Through Everyone is a Teacher Here (ETH) Learning Model - Romi Yanda; Istihana Istihana; Sunarto Sunarto (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The low achievement of student learning outcomes in Islamic and character education at Junior High School 15 Krui demands innovative strategies. The Everyone Is a Teacher Here (ETH) model encourages active participation, peer dialogue, and critical reflection to optimize students' competencies. This study aims to test the effectiveness of the ETH model in optimizing Islamic and character education learning outcomes. A quantitative approach with a quasi-experimental design was used. The population comprised 93 eighth-grade students; simple random sampling assigned class VIII-2 (n = 47) as the experimental group and class VIII-1 (n = 46) as the control. The experimental group received treatment over three meetings using seven ETH syntaxes, while the control group followed conventional learning. The research data was comprehensively collected from the respondents, and the instrument was declared valid and highly reliable (Cronbach's alpha: 0.89). Data was analyzed using an independent samples t-test. The results showed a statistically genuine and significant difference in learning outcomes between the experimental and control groups (t = -2.504; p = 0.015 < 0.05). The experimental group achieved a substantially more optimal academic impact, confirming that the dynamic ETH syntax effectively boosts material mastery and fosters an active-collaborative classroom climate. In conclusion, implementing the ETH model significantly optimizes Islamic and character education outcomes. Practically, integrating ETH is highly recommended to facilitate adaptive, inclusive, and participatory learning that strengthens student competencies without relying heavily on high-level technological infrastructure.